A cross-modal feedback scheme for control of prosthetic grasp strength. (August 2016) - Kaneris, Ioannis; Gibson, Alison; Artemiadis, Panagiotis
Introduction: Given the lack of haptic feedback inherent in prosthetic devices, a natural and adaptable feedback scheme must be implemented. While multimodal feedback has proven successful in aiding dexterous performance, it can be mentally tasking on the individual. Conversely, cross-modal schemes relying on sensory substitution have proven to be equally effective in aiding task performance without cognitively burdening the user to the same degree. Objectives: This experiment investigated the effectiveness of the cross-modal feedback scheme through using audio feedback to represent prosthetic grasping strength during dynamic control of a prosthetic hand. Methods: A total of five individuals participated in two sets of experiments (four subjects in the first, one subject in the second). Participants were asked to control the grasping strength exerted by a prosthetic hand while using real-time audio feedback in order to reach up to three different levels of force within a trial set. Results: The cross-modal feedback scheme successfully provided users with the robust ability to modulate grasping strength in real-time using only audio feedback. Conclusion: Audio feedback effectively conveys haptic information to the user of a prosthetic hand. Retention of the training knowledge is evident and can be generalized to perform new (i.e. untrained) tasks.